The Influence of Servant Leadership and Organizational Culture on Work Engagement at the Southeast Sulawesi TVRI Office - Ramadhan, Muhammad Afdal Reski; Nurwati, Nurwati; Saleh, Salma (International Journal of Management and Education in Human Development, 2024)
The purpose of this study is to test and explain the Influence of Servant Leadership and Organizational Culture on Work Involvement at the Republic of Indonesia Television (TVRI) Office in Southeast Sulawesi, both simultaneously and partially. The research approach is a survey with Explanatory research. Data collection was carried out using an instrument in the form of a questionnaire. The population of this study were permanent employees at the Television Republic of Indonesia (TVRI) Southeast Sulawesi office with a sample of 54 people. The analysis tool used for the hypothesis is Multiple Linear Regression analysis. The research results show that the Servant Leadership variable partially has a negative and significant effect on work engagement; Organizational culture partially has a positive and significant effect on work engagement; as well as servant leadership and organizational culture simultaneously have a positive and significant effect on work engagement at the Televisi Republik Indonesia (TVRI) Southeast Sulawesi office.